Recent Record of Limenitis rileyi Tytler, 1940 (Insecta: Lepidoptera: Nymphalidae: Limenitidinae) from Upper Dibang Valley, Arunachal Pradesh, India - Singh, Arun P. (Indian Forester, 2017)
No Abstract.